Determinants of the crime rate in Argentina during the '90s - Cerro, Ana María; Meloni, Osvaldo (Estudios de Economía, 2016)
Based on Becker’s theoretical model, the present paper estimates econometrically the determinants of the crime rate in Argentina for the 1990-1999 period. Like previous empirical applications for Argentina, a significant deterrence effect was found. However unlike them we find a strong socio-economic effect on the crime rate. The unemployment rate and the income inequality indicator were found to have a positive and significant effects on the crime rate.